1979
DOI: 10.1016/0035-9203(79)90220-7
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine-resistant Plasmodium falciparum malaria in Kenya

Abstract: A case of chloroquine-resistant Plasmodium falciparum malaria in a non-immune male is reported. Primary attack came 19 days after return to a non-malarious country from a visit to Kenya. Recrudescences occurred three times with intervals of 30 to 33 days after standard chloroquine treatment. The WHO extended field test for sensitivity of falciparum malaria to chloroquine was followed by recrudescence 31 days later. Treatment with Fansidar terminated the infection. If continuous treatment of the patient with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(46 citation statements)
references
References 4 publications
1
43
0
2
Order By: Relevance
“…Chloroquine-resistant P. falciparum that originated along the Thailand-Cambodia border expanded to neighboring countries by the mid1960s, and to central India by the late 1970s (2). Notably, this resistant lineage reached the African continent in 1974 (44) and had dispersed to East Africa by the early 1980s (45)(46)(47)(48), to Central Africa in the mid-1980s (49-51), and to West Africa by the late 1980s (52)(53)(54)(55). The other chloroquine-resistant lineage that originated along the Panama-Colombia border was detected in Brazil in 1961, and had spread to South American endemic regions by the early 1980s (2).…”
Section: -1 Chloroquinementioning
confidence: 99%
“…Chloroquine-resistant P. falciparum that originated along the Thailand-Cambodia border expanded to neighboring countries by the mid1960s, and to central India by the late 1970s (2). Notably, this resistant lineage reached the African continent in 1974 (44) and had dispersed to East Africa by the early 1980s (45)(46)(47)(48), to Central Africa in the mid-1980s (49-51), and to West Africa by the late 1980s (52)(53)(54)(55). The other chloroquine-resistant lineage that originated along the Panama-Colombia border was detected in Brazil in 1961, and had spread to South American endemic regions by the early 1980s (2).…”
Section: -1 Chloroquinementioning
confidence: 99%
“…At about the same time, chloroquine resistance also appeared in South America (Moore and Lanier, 1961). Chloroquine resistance appeared later in Africa, initially in nonimmune travelers returning from East Africa (Campbell et al, 1979;Fogh et al, 1979Fogh et al, , 1984Jepsen et al, 1983). Despite the current high levels of chloroquine resistance in most areas of malaria transmission, the cost of less than $0.20 U.S. per treatment continues to apply sufficient financial incentive to maintain chloroquine as a first-line treatment in much of West and Central Africa (Foster, 1994).…”
Section: Mechanisms Of Resistance Of Malaria Parasites To Antifolatesmentioning
confidence: 99%
“…A recent population genetic survey has shown that despite the close proximity, strains from PNG are remarkably different from those from Southeast Asia (133). In Africa, CRPF was first found in 1978 in nonimmune travelers from Kenya and Tanzania (34,72). This was followed 2 to 3 years later by reports from Madagascar (11) and by reports in semi-immune patients in Tanzania (106,155) and Kenya (128,193).…”
Section: Emergence Of Chloroquine-resistant P Falciparummentioning
confidence: 99%